THE ROLE OF SCHOOL ENVIRONMENT IN CULTIVATING MORALS IN ELEMENTARY SCHOOL AGE CHILDREN AT SDN 15, LUBUKLINGGAU CITY - Pajaria (Teaching and General Education Studies, 2025)
The school environment is a unified space in a formal educational institution that systematically implements guidance programs to help students develop their potential optimally, covering moral, spiritual, intellectual, emotional, social, and physical-motor aspects. Schools are not merely places for the "transfer of knowledge." The background of this research is the observed low respect among children at SDN 15 Lubuklinggau, where the principal acknowledged students’ generally good behaviour but insufficient respect toward parents. The school aims to strengthen the spiritual side based on family principles. The objective of this study is to describe and analyse the cultivation of moral values in elementary school children. The approach used in this study is a qualitative approach, intended to describe and analyse phenomena, social activities, and perceptions systematically and in depth. This research is qualitative descriptive, with data collected through observation, interviews, and documentation. The results indicate that the school environment at SDN 15 Lubuklinggau fosters moral development through daily religious practices, teacher modelling, and integration of moral values in lessons, although challenges remain in consistency and parental involvement. The conclusion highlights that a supportive, family-like school environment is effective in promoting moral values but requires active collaboration between teachers and parents. This research implies the need for structured moral education programs and suggests future studies explore parental engagement strategies to reinforce moral cultivation in children.